2011
DOI: 10.1063/1.3665877
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and short-range structure analysis of granular cobalt silicon nitride multilayers

Abstract: Effects of spacer thickness on perpendicular anisotropy L10-FePt/TiN/L10-FePt pseudo spin valves J. Appl. Phys. 111, 083909 (2012) Co/Au multilayers with graded magnetic anisotropy for magnetic field sensing Appl. Phys. Lett. 100, 162402 (2012) Design and micromagnetic simulation of the L10-FePt/Fe multilayer graded film J. Appl. Phys. 111, 073910 (2012) Precession frequency and fast switching dependence on the in-plane and out-of-plane dual spin-torque polarizers Appl. Phys. Lett. 100, 142409 (2012) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…However, both the pre-edge and white line did not reach the same levels as those observed for the cobalt metallic foil, indicating that cobalt atoms remained partially oxidized. To the best of our knowledge, only two experimental studies have reported the XANES spectrum of Co III N, either as a rock-salt-type or a zinc-blende-type structure . The formation of CoN (ZnS type) was excluded for CoO x /Ta 3 N 5 because of the absence of the intense and well-resolved transition Co­(1s) → Co­(3d-4p), related to the local tetrahedral symmetry around the cobalt atoms (Wyckoff position 4a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both the pre-edge and white line did not reach the same levels as those observed for the cobalt metallic foil, indicating that cobalt atoms remained partially oxidized. To the best of our knowledge, only two experimental studies have reported the XANES spectrum of Co III N, either as a rock-salt-type or a zinc-blende-type structure . The formation of CoN (ZnS type) was excluded for CoO x /Ta 3 N 5 because of the absence of the intense and well-resolved transition Co­(1s) → Co­(3d-4p), related to the local tetrahedral symmetry around the cobalt atoms (Wyckoff position 4a).…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, only two experimental studies have reported the XANES spectrum of Co III N, either as a rock-salt-type 63 or a zinc-blende-type structure. 64 The formation of CoN (ZnS type) was excluded for CoO x /Ta 3 N 5 because of the absence of the intense and well-resolved transition Co(1s) → Co(3d-4p), related to the local tetrahedral symmetry around the cobalt atoms (Wyckoff position 4a). A minor presence of CoN with a rock-salt-type structure cannot be ruled out because the pure compounds display a rather intense white line with a quasi-inexistent pre-edge transition (Co in O h symmetry).…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…In particular, metal-ceramic multilayers show an attractive combination of electrical [3,4], magnetic [5][6][7], optical [8][9][10] and mechanical [11] properties, which are appealing for a number of engineering applications. For instance, metal-ceramic nanolaminates offer a good combination of hardness and toughness, leading to excellent wear resistance for protective coatings [11,12].…”
Section: Introductionmentioning
confidence: 99%